The heart failure epidemic: a UK perspective - Martin R Cowie (Echo Research and Practice, 2017)
Heart failure is appropriately described as an epidemic, with 1–2% of health care expenditure being directed at its management. In England, the National Institute for Health and Care Excellence (NICE) has issued guidance on the best practice for the diagnosis and treatment of acute and chronic heart failure. Echocardiography is key to the diagnosis of the underlying cardiac abnormalities, and access to this (with our without biochemical testing using natriuretic peptides) is key to high-quality and speedy diagnosis. New models of care aim to speed up access to echocardiography, but a shortage of technically trained staff remains a limiting factor in improving standards of care. The NHS audits the quality of care and outcome for patients admitted to hospital with heart failure, and this continues to show wide variation in practice, particularly, where patients are not reviewed by the local heart failure multidisciplinary team. Recently, the All Party Parliamentary Group on Cardiac Disease issued 10 suggestions for improvement in care for patients with heart failure – access to echocardiography being one of the key suggestions. Time will tell as to whether this support from law makers will assist in the implementation of NICE-recommended standards of care consistently across the country.